Growth Performance and Digestive Enzyme Activity of Broiler Fed with Microwaved Flaxseed Flour (Linum usitatissimum) - Rosyidatul Churriyah; O Sofjan; M H Natsir (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
This research aimed to evaluate the effect of the use of microwaved flaxseed flour as broiler feed on the growth performance and digestive enzyme activity. The material used was 200 a-day-old chicks strain Lohmann MB Platinum. The method of this research was in vivo feeding trial using a Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments included the use of flaxseed flour with levels of 0% (T0), 2.5% (T1), 5% (T2), 7.5% (T3), and 10% (T4). The variables measured were feed intake, body weight gain, feed conversion ratio, mortality, amylase, and protease activity. The data obtained were analyzed by Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DMRT). The result showed that the treatments highly significant (p<0.01) increasing the amylase activity and decreasing the protease activity, but had no significant effect on the feed intake, body weight gain, feed conversion ratio, and mortality. It can be concluded that the use of microwaved flaxseed flour up to 10% did not give negative effect on broiler, but 2.5% showed the best result compared to other treatments. Key words: broiler, digestive enzyme activity, flaxseed flour, growth performance, microwave